The bandit, a new DNA transposon from a hookworm-possible horizontal genetic transfer between host and parasite. - Thewarach Laha; Alex Loukas; Supatra Wattanasatitarpa; Jenjira Somprakhon; Nonglack Kewgrai; Paiboon Sithithaworn; Sasithorn Kaewkes; Makedonka Mitreva; Paul J Brindley (Public Library of Science (PLoS), 2007)
An enhanced understanding of the hookworm genome and its resident mobile genetic elements should facilitate understanding of the genome evolution, genome organization, possibly host-parasite co-evolution and horizontal gene transfer, and from a practical perspective, development of transposon-based transgenesis for hookworms and other parasitic nematodes.A novel mariner-like element (MLE) was characterized from the genome of the dog hookworm, Ancylostoma caninum, and termed bandit. The consensus sequence of the bandit transposon was 1,285 base pairs (bp) in length. The new transposon was flanked by perfect terminal inverted repeats of 32 nucleotides in length with a common target site duplication TA, and it encoded an open reading frame (ORF) of 342 deduced amino acid residues. Phylogenetic comparisons confirmed that the ORF encoded a mariner-like transposase, which included conserved catalytic domains, and that the bandit transposon belonged to the cecropia subfamily of MLEs. The phylogenetic analysis also indicated that the Hsmar1 transposon from humans was the closest known relative of bandit, and that bandit and Hsmar1 constituted a clade discrete from the Tc1 subfamily of MLEs from the nematode Caenorhabditis elegans. Moreover, homology models based on the crystal structure of Mos1 from Drosophila mauritiana revealed closer identity in active site residues of the catalytic domain including Ser281, Lys289 and Asp293 between bandit and Hsmar1 than between Mos1 and either bandit or Hsmar1. The entire bandit ORF was amplified from genomic DNA and a fragment of the bandit ORF was amplified from RNA, indicating that this transposon is actively transcribed in hookworms.A mariner-like transposon termed bandit has colonized the genome of the hookworm A. caninum. Although MLEs exhibit a broad host range, and are identified in other nematodes, the closest phylogenetic relative of bandit is the Hsmar1 element of humans. This surprising finding suggests that bandit was transferred horizontally between hookworm parasites and their mammalian hosts.